Pretreatment of epithelial cells with live Streptococcus pneumoniae has no detectable effect on influenza A virus replication in vitro. - Kang Ouyang; Shireen A Woodiga; Varun Dwivedi; Carolyn M Buckwalter; Anirudh K Singh; Basavaraj Binjawadagi; Jagadish Hiremath; Cordelia Manickam; Rose Schleappi; Mahesh Khatri; Jianmin Wu; Samantha J King; et al. (PLoS ONE)
Influenza A virus (IAV) and Streptococcus pneumoniae (pneumococcus) are two major upper respiratory tract pathogens responsible for exacerbated disease in coinfected individuals. Despite several studies showing increased susceptibility to secondary bacterial infections following IAV infection, information on the direct effect of S. pneumoniae on IAV in vitro is unknown. This is an important area of investigation as S. pneumoniae is a common commensal of the human upper respiratory tract, present as an important coinfecting pathogen with IAV infection. A recent study showed that S. pneumoniae enhances human metapneumovirus infection in polarized bronchial epithelial cells in vitro. The aim of the current study was to determine whether treatment of epithelial cells with S. pneumoniae affects IAV replication using a standard immunofluorescence assay (IFA). For this study we used four IAV permissive epithelial cell lines including two human-derived cell lines, 12 pneumococcal strains including recent human clinical isolates which represent different genetic backgrounds and serotypes, and six IAV strains of varying genetic nature and pathogenic potential including the pandemic 2009 H1N1 virus. Our results suggested that pretreatment of MDCK cells with 7.5×10(6) colony-forming units (CFUs) of live S. pneumoniae resulted in gradual cell-death in a time-dependent manner (0.5 to 4 hr). But, pretreatment of cell lines with 7.5×10(5) and lower CFUs of S. pneumoniae had no detectable effect on either the morphology of cells or on the IAV replication. However, unlike in epithelial cell lines, due to influence of secreted host factors the effect of pneumococci on IAV replication may be different during coinfections in vivo in the human upper respiratory tract, and in vitro with primary human polarized bronchial epithelial cells.